(untitled) (Journal of Multidisciplinary Sciences and Innovations, 2025)
This article analyzes the theoretical issues of long-term assets in accounting. In various approaches, such assets in regulatory documents are presented as resources purchased by enterprises for shares, bonuses or long-term exploitation. Also, long-term financial investments and assets recognized as investment property are considered one of the effective directions for future capital investment. Therefore, it is urgent to reconsider the classification and characteristics of long-term assets.